Robust L_p-Norm Decoding for BICM-Based Secondary User Systems - Nasri, Amir; Schober, Robert (IEEE transactions on communications, 2010)
The frequency bands used by secondary user systems such as cognitive radio and ultra--wideband (UWB) systems are subject to various forms of non--Gaussian noise and interference including co--channel and narrowband interference caused by the primary user and other secondary users as well as man--made impulsive noise. For secondary user systems employing popular bit--interleaved coded modulation (BICM) we propose a robust L_p--norm metric for Viterbi decoding to overcome the harmful effects of non--Gaussian noise and interference. For the resulting system, we derive an approximate upper bound on the bit error rate (BER) and a general analytical expression for the asymptotic BER valid for all practically relevant types of fading, including Rayleigh, Ricean, Nakagami--m, Nakagami--q, and Weibull fading, and all types of noise and interference with finite moments. Simulation and analytical results show that, in non--Gaussian noise and interference, the proposed L_p--norm metric yields large performance gains over the conventional L_2--norm metric and outperforms erasure decoding.